The mediating role of inflammatory biomarkers in the association between serum copper and sarcopenia - Dapeng Zeng; Bo Chen; Hao Wang; Shenghao Xu; Shibo Liu; Zehao Yu; Xiangjun Pan; Xiongfeng Tang; Yanguo Qin (Scientific Reports)
Abstract This study aims to investigate the association between serum copper (Cu), selenium (Se), zinc (Zn), Se/Cu and Zn/Cu ratios and the risk of sarcopenia. In this study, which involved 2766 adults aged ≥ 20 years enrolled in the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2016, multivariable logistic regression, restricted cubic spline (RCS) models and mediation analyses were used. After full adjustment, multivariable logistic regression revealed that higher serum copper levels were correlated with an increased risk of sarcopenia. Conversely, higher serum Se/Cu (OR 0.45, 95% CI 0.23–0.89, P = 0.023) and Zn/Cu (OR 0.49, 95% CI 0.27–0.90, P = 0.024) were associated with a decreased risk of sarcopenia. The RCS curve indicated a non-linear, roughly inverted L-shaped relationship between serum Cu and sarcopenia risk (P non-linear < 0.001). Additionally, Se/Cu (P non-linear = 0.179) and Zn/Cu (P non-linear = 0.786) showed negative linear associations with sarcopenia risk. Furthermore, white blood cell (WBC) count, neutrophil count, and systemic inflammation index (SII) were identified as significant mediators in the relationship between serum Cu and the risk of sarcopenia, with mediation proportions of 6.34%, 6.20%, and 4.37%, respectively (all P < 0.05). Therefore, balancing essential trace metals is crucial for maintaining muscle health.